Comparison between shear forces applied on the overlay-dental tissue interface using different bonding techniques: An in vitro study - Thomas Reboul; H A Hoang Thaï; Sibel Cetik; Ramin Atash (Wolters Kluwer Medknow Publications, 2018)
Aim: The aim of this study was to compare the adhesion of glass-ceramic overlays to tooth structure, under the effect of shear forces, using different bonding systems. Materials and Methods: Thirty healthy lower third molars were selected and randomly allocated into three groups (n = 10). Group 1: overlays bonded to tooth structure using Panavia V5 with immediate dentin sealing (IDS); Group 2: overlays bonded using Panavia V5 without IDS; and Group 3: overlays bonded using heated composite combined with a bonding agent with IDS. All the restorations were made of glass-ceramic (Suprinity, Vita). The restored teeth were then stored in distilled water for 7 days and at room temperature. Shear forces were applied using a universal testing machine. Load and displacement were recorded at intervals of 0.1 s. A statistical analysis was used to compare the groups. Results: The mean resistance to fractures ± standard deviation obtained for the Groups 1, 2, and 3 was, respectively, 15.7440 ± 2.13, 12.0750 ± 1.41, and 8.33364 ± 2.85 MPa. The analysis of variance was highly significant (P < 0.001) allowing us to reject the null hypothesis of equality between the three groups. Comparisons between pairs also provided significant results. Conclusion: Bonding using Panavia V5 with IDS showed a better resistance to shear forces when compared to other bonding techniques. The application of IDS increased the adhesion.